STUDI PERENCANAAN JEMBATAN BETON TIPE STRUKTUR PLAT MENERUS DENGAN TULANGAN DUA ARAH - Joni, I Gede Putu (Jurnal Ilmiah Teknik Sipil, 2016)
The bridge is an important component in the transportation system, as it determines the capacity and service level of transportation system itself. Therefore the failure of the bridge with various courses should be avoided. Given the importance of the bridge roles in the transportation system will require good planning by considering the various of planning, such as aspects of marine and stability, stiffness, durability (purability), tractable (workability), economical (cash effective) and aesthetic aspects, and supported by the traffic data and soil data, as well as regulation for bridge planning PPJR 1987 and BMS 1992. Consider the economic aspects as a necessity in today’s era of global competition, without prejudice to other parameters and factor of safety for users of transportation system.
Keywords: Bridge, Security, Economical